Assessing Lower Secondary School Students' Common Errors in Statistics. - Lim Hooi Lian; Wun Thiam Yew; Chew Cheng Meng (Pertanika Journal of Social Sciences & Humanities, 2022)
Statistical literacy has been emphasised in the school mathematics curriculum, with the growing concern about students' ability to think critically in solving statistical problemsolving tasks. However, the current studies revealed that secondary school students' errors mainly involve the problem of basic concepts in statistics, data interpretation, and the selection of an appropriate representation of data. Therefore, this study aimed to analyse the common errors made by students in solving statistics tasks with multi-level complexity. A survey method was applied in this study. The sample of this study consisted of 356 Form One (Grade 7) students from eight secondary schools. The instrument of this study consisted of five superitem tasks, which represented the five content domains: line graph, bar graph, pie chart, dot plot, and histogram. There are four levels of items in each superitem task. Thus, the total number of items is 20. The format of all the 20 items in the five superitem tasks is open-ended. The common errors were then analysed based on all the participants' solutions shown in their answer script. The findings found that most students could not achieve the highest level of statistical competency. They failed to think qualitatively while justifying data. This study provides a meaningful analysis that assists the teaching and learning of statistics to better link numeracy and literacy. The application of the superitem tasks provides valuable information that enables the teachers to understand their students' statistical processes better.